The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/mpg.0000000000001272
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Bifidobacterium animalis Subsp. Lactis (B. lactis) Strain BB‐12‐Supplemented Yogurt in Healthy Children

Abstract: Objectives Probiotics are live microorganisms that may provide health benefits to the individual when consumed in sufficient quantities. For studies conducted on health or disease endpoints on probiotics in the United States, the Food and Administration (FDA) has required those studies to be conducted as investigational new drugs. This phase I, double-blinded, randomized, controlled safety study represents the first requirement of this pathway. The purpose of the study was to determine the safety of Bifidobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 48 publications
4
23
0
Order By: Relevance
“…To complete our strain selection, we investigated the hydratase activity of two further bacteria, namely Bacillus coagulans (Colinox ® ) and Streptococcus salivarius (ATCC BAA 1024) as well as that of Saccharomyces boulardii (SB80 ® , CNCM I-3799), which is the only yeast widely used as a probiotic. All these microorganisms are commercially available because they are currently used to restore the gut and oral cavity flora and thus improve human health [43][44][45][46][47][48][49][50][51][52][53][54][55].…”
Section: Resultsmentioning
confidence: 99%
“…To complete our strain selection, we investigated the hydratase activity of two further bacteria, namely Bacillus coagulans (Colinox ® ) and Streptococcus salivarius (ATCC BAA 1024) as well as that of Saccharomyces boulardii (SB80 ® , CNCM I-3799), which is the only yeast widely used as a probiotic. All these microorganisms are commercially available because they are currently used to restore the gut and oral cavity flora and thus improve human health [43][44][45][46][47][48][49][50][51][52][53][54][55].…”
Section: Resultsmentioning
confidence: 99%
“…Two general probiotic approaches have been taken to influence the infant or child microbiota. The first approach is to administer the probiotic to the mother during pregnancy Fecal pH: SCF 20 g < control, SCF 10 g ↔ SCFA concentrations [56] and then to either the mother and/or infant postpartum [63][64][65][66][67][68][69][70] (Table 3), and the second is to administer the probiotic directly to the infant or child [71][72][73][74][75][76][77][78][79][80][81][82][83][84] (Table 4). For the first approach, most studies gave probiotics to the mothers of infants with high-risk of allergy, with the goal of prevention of allergic disease, such as eczema, asthma and allergic rhinitis [63-65, 69, 70].…”
Section: Probiotic Interventions In Children On Gut Microbiotamentioning
confidence: 99%
“…Systematic reviews investigating the safety of probiotics have concluded that their use in humans does not lead to an increase in the risk of adverse events 29 , 30 . Since these meta-analyses, several additional phase 1 safety studies have been conducted, also documenting safety of certain probiotics used in different population groups 31 34 . However, safety has not been assessed thoroughly in many studies 29 , 30 , and some vulnerable patients in specific condition have also been identified at higher risk for adverse events in case of probiotic consumption 29 .…”
Section: Introductionmentioning
confidence: 99%